Future cities, resilient cities – The role of underground space in achieving urban resilience - Han Admiraal; Antonia Cornaro (Underground Space, 2020)
The need for future cities to be resilient stems from the fact that now more than ever in history, both natural and human-made hazards are threatening cities in the forms of shocks and stresses. The ability of cities to resist or restore themselves following these events is dependent on their resilience.As we now firmly enter the Anthropocene, the geological epoch in which human activity, for the first time in history is directly influencing the Earth’s systems, we need to develop resilient cities that can cope with the increase in hazards. Although climate change is one factor influencing urban resilience, it is not the only one. A lack of understanding of the subsurface can also influence a city’s resilience, as can the unplanned use of its underground spaces. In planning and developing our cities of the future, a deep understanding of the geology that supports the city is required not only to be able to determine the possibilities of future use but also to determine whether there are natural processes that could threaten human existence over time. The destruction of ecosystem services through unchecked human activities could be one of these activities. In this paper, the authors will investigate how the subsurface and use of underground spaces can influence urban resilience. The role that underground spaces can play in achieving urban resilience for our future cities will be described.